Childcare allowance for farmers and household members insured with the Agricultural Social Insurance Fund - Puślecki, Damian (Przegląd Prawa Rolnego, 2021)
The aim of this paper was to answer the question to what extent the unique construction of the right to the childcare allowance, taken over from the general social insurance, provides protection for entities conducting agricultural activity. The author concludes that granting farmers the right to the childcare allowance was an unprecedented move on the part of the legislator, justified by the need to support agricultural activity during the period of COVID-19 pandemic. However, the institution of the right to “Covid agricultural carer’s allowance” was regulated in a fragmentary way and is only of transitional character, having been established outside the agricultural social insurance system. Due to the small amount of the granted benefit, it cannot perform a compensatory-supportive-incentive function adequately.